Analisis Aspek Produksi Dalam Studi Kelayakan Bisnis - Friska Olavia Sitorus; Rahmatul Fadilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
A business feasibility study is a study for an investment or business to be considered feasible or not to run because the investment in question is relatively large in value. The method of assessment is by conducting studies or research on investment or business aspects, one of which is the production aspect. Aspects of production are very important a business activity oriented to the sale of a product. Product planning and development is essentially a wide range of marketing activities and it is a consumer-oriented function. This study aims to analyze the production aspect in a business feasibility study. Keywords: Production, Business Feasibility Study, Aspects of Feasibility Study